BEL422: Report Writing / Academy of Language Studies - UiTM, Academy of Language Studies (2012)
This course introduces students to the practical aspects of preparing and presenting reports both orally and in written form. Students are taught to employ the language skills and strategies necessary to write a report based on a combination of primary and secondary research. Students will also be taught the skills of adapting the written report for oral presentation.